Morpho-histological comparative study of the liver in White-eared bulbul (Pycnonotus leucotis), Mallard duck (Anas platyrhynchos), and Gull (Larus canus) - Al-Khazraji, Khalid Ibrahim Abd (The Iraqi Journal of Veterinary Medicine, 2018)
This study was conducted to compare some of anatomical features and histological structure of the liver in three species of birds that varied in their size, taxonomy, and food environment. The study revealed that the liver in the mallard, gull and white-eared bulbul was bilobed big gland, and the left lobe was smaller than the right one. It was observed that the two lobes in mallard were undivided, while the right lobe in gull has two parts, whereas the left lobe in white-eared bulbul is subdivided into two parts. Histologically, the liver capsule in gull appeared thicker than other two species. The hepatic parenchyma was not shown to be clearly defined lobules in three species. The hepatocytes were organized radially around the central vein as plates or cords of one-two cell thick in mallard and gull, and of two-several cell thick in white-eared bulbul, and those plates were separated by blood sinusoids. It turned out that the hepatic portal triads were less numerous in white-eared bulbul compared with other two species. It was found that there are differences in measurements of some histological structures of the liver among the three species.